The Art-gallery in the desert - Gotoh, Isamu; Kikuchi, Harou; Tagawa, Junzo; Tamai, Isao.; CCTV (China).; NHK Enterprises, Inc. (Japan). ([S. l.] NHK, 1990)
Explores the world-famous Ma-gao Caves at Dun-Huang - over 500 caves. More than 30 miles in length, with 3,000 murals and status - in the middle of the Gobi Desert. Dating from 366 A.D. and encompassing the art styles of Greece, India and the many dynasties of China, these caves hand-tunnelled into the Mingsha mountains are a tour-de-force of religious art.
VHS.
Music by Kitaro; Edited by Hiroyuki Shoji; Narrated by Graham Webster.
Keywords: Art museum -- China; Art, Chinese; Caves -- China; Silk Road; China -- Antiquities; China -- Description and travel; China -- History